WAGES IN READING AL-QUR'AN AT THE GRAVE - Lannasari Hasibuan, Fatahuddin Aziz Siregar, & Ikhwanuddin Harahap (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
The problem of this research lies in the practise of setting wages for services to read the Qur’an at the graves of people who have just died with a certain number and determined by the party renting commercializing the reading of the Qur’an. The main pupose of implementation gurading graves of people who have just died is to help mayit in his barzakh, recitation of Qur’an as a helping media for mayit. Usually society carried out this guarding grave for their family or their parents which as long as their live in the world  ignore their obligation to God of Allah and they had worse morals,  as their faith to the spririt of their family or their parent’s spirit they looking for the people who has been prepare the service for reading the Qur’an at their graves and the recitation as a prayer for the spirit. To guarding the grave the reader had make a rate for a night as much as IDR. 1.000.000 it can be increase and can be decrease according to the agreement of two parties in their contract and based on the conditions of the the object in ijarah, this practise have not been fulfilled as a whole, namely the point of benefit the object ability of the object to be transacted in an ijarah agreement and this object  include in an obedient of the heirs to pray for their parent’s spirit. This research written by qualitative descriptif method with data collection techniques in the form of observation, interviews, documenation, and additional book as a literature references. The main discusssin in this research is an implementation of wages in reading the Qur’an at the grave and review of fiqh muamalah about that implementation. In fiqh muamalah review the implementation of reading the Qur’an in the grave with the rate of payment is forbidden in Islam based on narrative hadits “read the Qur’an and do not take eat something from it” read the Qur’an at the grave is allowed but not to be commercial to take much money from worship work Based on agreement of ulama Mazhab Maliki  and Syafi’i allowed to take repayment from the Qur’an (as not to be commercializing)  while Hanafi and Hanbali didn’t allowed to take repayment from the Qur’an and based on the benefit of the object of ijarah is not fulfilled and the object ability to be transacted.